(2^x) (30^3) = (2^3) (3^3) (4^3) (5^3)

(2^x) (30^3)=(2^3)(3^3)(4^3)(5^3) (2^x)(30^3)=((2*3*4*5)^3) (2^x)=((2*3*4*5)^3) / (30^3) (2^x)=((2*3*4*5/30)^3) (2^x)=(4^3) (2^x)=((2^2)^3) (2^x)=(2^6) which implies x=6.

x=6

the value of x = 6.

(2^x)(30^3)=(2^3)(4^3)(5^3)(3^3) (2^x)((2x3x5)^3)=(2^3)(4^3)(5^3)(3^3) (2^x)((2x3x5)^3)=(2^3)(((2)^2)^3)(5^3)(3^3) (2^x)(2^3)(3^3)(5^3)=(2^9)(5^3)(3^3) (2^3x)(3^3)(5^3)=(2^9)(5^3)(3^3)

equating, 3x=9 x=3

Find the value of x in the following equation?

Can you solve this equation to get the value of x?

What is the value of x which satisfies the following equation?